2019
DOI: 10.3390/f10020078
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Nitrogen Addition Does Not Significantly Alter the Effects of Seasonal Drought on Leaf Functional Traits in Machilus pauhoi Kanehira Seedlings

Abstract: Research Highlights: Short-term nitrogen (N) addition did not significantly alter the effects of seasonal drought on the leaf functional traits in Machilus pauhoi Kanehira seedlings in N-rich subtropical China. Background and Objectives: Seasonal drought and N deposition are major drivers of global environmental change that affect plant growth and ecosystem function in subtropical China. However, no consensus has been reached on the interactive effects of these two drivers. Materials and Methods: We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…Correlations were more consistent in gymnosperms, likely because evergreens such as P. koraiensis often hold more mechanical tissues which could help avoiding damage as result of frost or drought [ 59 ]. In previous studies LD of woody species was furthermore found negatively related to the fractions of epidermis and mesophyll but positively related to the fraction of sclerified tissues [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In partial contrast to our second hypothesis we did not find correlations of LD (and LT) with epidermis and mesophyll thicknesses in the studied gymnosperms; variable cell sizes and number [ 19 , 60 ] and air spaces may thus explain differences in LD (and LT) beside changes in structural tissue fractions [ 14 , 46 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Correlations were more consistent in gymnosperms, likely because evergreens such as P. koraiensis often hold more mechanical tissues which could help avoiding damage as result of frost or drought [ 59 ]. In previous studies LD of woody species was furthermore found negatively related to the fractions of epidermis and mesophyll but positively related to the fraction of sclerified tissues [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. In partial contrast to our second hypothesis we did not find correlations of LD (and LT) with epidermis and mesophyll thicknesses in the studied gymnosperms; variable cell sizes and number [ 19 , 60 ] and air spaces may thus explain differences in LD (and LT) beside changes in structural tissue fractions [ 14 , 46 ].…”
Section: Discussionmentioning
confidence: 88%
“…While some previous studies indicated that greater N deposition rates may reduce the growth and/or decrease the leaf area due to a toxic effect of ammonium on certain tree species, incl. F. mandshurica [ 43 , 44 ], this was not the case for the studied species under given experimental conditions—indicating that observed effects on leaf traits are indeed based on a varied N availability.…”
Section: Discussionmentioning
confidence: 99%
“…N addition mediates the effect of drought on soil water content reduction. The response of arid grassland to drought is stronger (Dziedek et al 2016), and N addition could decrease plants' drought resistance (Yu et al 2019). However, the carbon and nitrogen content and bulk density of soil did not respond signi cantly to such short-term habitat changes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we uncovered changes in CWMs for most of the traits, and the contribution of inter- and intraspecific variation. N addition increased LNC and decreased C: N at both species- and community-level in the two steppes, indicating that N addition enhanced the availability of N nutrients and in turn reflected a shift towards a rapid resource absorption and growth strategy [ 43 ], and a decrease in the C:N is results from elevated LNC and a relatively stable carbon level under N addition [ 44 ]. Moreover, drought caused an increase in LNC of the meadow steppe, supporting the finding that suggested increased LNC with increasing drought [ 45 ].…”
Section: Discussionmentioning
confidence: 99%